Comparison of hydrogen micromix flame transfer functions determined using RANS and LES - McClure, Jonathan; Abbott, David; Agarwal, Parash; Sun, Xiaoxiao; Babazzi, Giulia; Sethi, Vishal; Gauthier, Pierre Q. (ASME, 2019)
Hydrogen has been proposed as an alternative fuel to meet long term emissions and sustainability targets, however due to the characteristics of hydrogen significant modifications to the combustion system are required. The micromix concept utilises a large number of miniaturised diffusion flames to improve mixing, removing the potential for local stoichiometric pockets, flash-back and autoignition. No publicly available studies have yet investigated the thermoacoustic stability of these combustion systems, however due to similarities with lean-premixed combustors which have suffered significant thermoacoustic issues, this risk should not be neglected. Two approaches have been investigated for estimating flame response to acoustic excitations of a single hydrogen micromix injector element. The first uses analytical expressions for the flame transfer function with constants obtained from RANS CFD while the second determines the flame transfer function directly using unsteady LES CFD. Results show the typical form of the flame transfer function but suggest micromix combustors may be more susceptible to higher frequency instabilities than conventional combustion systems. Additionally, the flame transfer function estimated using RANS CFD is broadly similar to that of the LES approach, therefore this may be suitable for use as a preliminary design tool due to its relatively low computational expense.
Keywords: Combustion chambers; Computational fluid dynamics; Combustion systems; Transfer functions; Reynolds-averaged Navier–Stokes equations; Hydrogen; Flames